Efficacy of ursodeoxycholic acid in reducing the necessity of cholecystectomy due to pre-existing and subsequently formed gallstones in patients who underwent laparoscopic sleeve gastrectomy - Muhammed Taha Demirpolat; Muhammet Oğuz Celikkaya; Suleyman Cağlar Ertekin; Fatih Basak; Abdullah Sisik (BMC Surgery)
Abstract Background In this study, we aimed to investigate whether ursodeoxycholic acid (UDCA) would reduce the necessity of cholecystectomy in patients diagnosed with asymptomatic gallstones after laparoscopic sleeve gastrectomy (LSG) and in patients diagnosed with asymptomatic gallstones before LSG. Methods Between July 2020 and November 2022, at least 2-year follow-ups of patients who underwent LSG for obesity were retrospectively analyzed. Patients with pre-existing asymptomatic gallstones during preoperative evaluation, those with UDCA treatment (group 1), and observation group (group 2). Patients with newly formed gallstones in postoperative outpatient clinic follow-up, those with UDCA treatment (group A), and those without UDCA treatment (group B). Results A total of 425 patients included. At the end of the first year, patients who had newly formed gallstones after LSG had a higher total weight loss percentages (TWL%) (39.8 ± 6.1) compared to those who did not develop gallstones (37.9 ± 7.4), which were statistically significant (p = 0.004). Among patients who developed gallstones postoperatively, UDCA treatment was associated with a significantly lower cholecystectomy rate in patients with newly formed gallstones postoperatively (p = 0.025), while no significant difference was shown in patients with preoperative gallstones (p = 0.631). Conclusion UDCA is a promising option for reducing the need for cholecystectomy in patients with post-LSG gallstones, but it appears ineffective for pre-existing gallstones.